The Role of In-House Training in Strengthening Teacher Professionalism in Inclusive Learning at Coastal Elementary Schools in Ketapang Regency - Sri Arsayati; mada sutapa (Journal of Education and Teaching Learning, 2026)
This study analyzes the role of In-House Training (IHT) in strengthening teacher professionalism in inclusive learning at coastal elementary schools in Ketapang Regency. The study employed a qualitative approach with a multi-site case study design at SD Negeri 01 Matan Hilir Selatan and SD Negeri 09 Matan Hilir Selatan. Data were collected through in-depth interviews, classroom observations, school environment observations, and document studies involving two principals and eight classroom teachers. Data were analyzed using the Miles, Huberman, and Saldana model through data condensation, data display, conclusion drawing, and verification. Data trustworthiness was strengthened through source triangulation, technique triangulation, member checking, and document auditing. The findings indicate that IHT plays a role in improving teachers’ understanding of student characteristics, differentiated instruction, adaptive strategies, and teacher collaboration. SD Negeri 01 Matan Hilir Selatan, which had implemented IHT, demonstrated stronger pedagogical readiness than SD Negeri 09 Matan Hilir Selatan, which had not conducted IHT. However, inclusive learning implementation still faces limited facilities, the absence of permanent special assistant teachers, unequal access to professional development, and geographical challenges in coastal areas. The study confirms that school-based IHT should be strengthened through principals’ academic supervision and local government policy support.